Pengaruh Environmental Performance dan Green Innovation Terhadap Competitive Advantage Studi Pada UMKM di Jakarta - Yuha Auliana; Luthfi Alhazami (Transformasi: Journal of Economics and Business Management, 2023)
With a total trash of 67.8 tons, Indonesia is one of the top five countries in the world for producing plastic waste. Environmental challenges make it difficult for businesses to develop new products that improve environmental sustainability, green purchasing, and responsible manufacturing. With this, work is meant to continue in the future. The purpose of this study is to ascertain the relationship between environmental performance and green innovation and the competitive advantage of MSMEs in Jakarta that have adopted green innovations. This study employed a quantitative methodology with a sample size of 80 participants. Questionnaires served as the study's main tool. Validity and reliability tests are two types of quality testing and instrumentation. Descriptive analysis and hypothesis testing were utilized in data analysis.